Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/978-3-642-15384-6_26
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Approach to Image Retrieval Using Statistical Models Based on a Lexical Ontology

Abstract: Abstract. The increasing amount of digital images available on the Internet has made searching, browsing, and organizing such resources a major challenge. This paper proposes a semantic approach to text-based image retrieval of manually annotated digital images. The approach uses statistical models based on Semantic DNA (SDNA) extracted from the structure of a lexical ontology called OntoRo. The approach involves three main techniques: (a) SDNA extraction, (b) word sense disambiguation using statistical models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The semantic meaning is identified by performing backtracking on the class hierarchy. The reasoner is used in checking the consistency of data in an ontology and performs semantic reasoning in the ontology (Fadzli and Shi, 2010).…”
Section: Semantic Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…The semantic meaning is identified by performing backtracking on the class hierarchy. The reasoner is used in checking the consistency of data in an ontology and performs semantic reasoning in the ontology (Fadzli and Shi, 2010).…”
Section: Semantic Searchmentioning
confidence: 99%
“…The SPARQL query language has been adopted by the W3C (World Wide Web Consortium) as the means to query ontologies built by using RDF and has been extended to support OWL format (Antoniou and Harmelen, 2004). The ontology guided reasoning is done by using the reasoner like Pallet, FaCT using SPARQL (Fadzli and Shi, 2010). The Fig.…”
Section: Semantic Searchmentioning
confidence: 99%
“…As defined in [8,9], an SDNA is a string of numbers derived from a lexical ontology. This study uses a lexical ontology called OntoRo developed based on the digital version of the Roget's Thesaurus [13].…”
Section: Lexical Ontologymentioning
confidence: 99%
“…An SDNA [8,9] is a string of numbers which represents a sense of word according to the hierarchical structure of a lexical ontology. Previous work has shown that the extraction of Semantic DNA based on SDNA similarities has a number of drawbacks including the SDNA weighting scheme which is based on the co-occurrences of SDNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, there are two types of image retrieval approaches: text-based image retrieval and contentbased image retrieval (CBIR). Text-based techniques [1,2] retrieve images by keywords. However, the traditional text-based techniques require manual labelling which is time-consuming and very subjective.…”
Section: Introductionmentioning
confidence: 99%